RECORD OF THE FROG CRAB, RANNINOIDES PERSONATUS HENDERSON, 1888 (CRUSTACEA: DECAPODA: RANINIDAE) - T. Vaitheeswaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The frog crab, Ranninoides personatus Henderson, 1888, were caught in the trawl net operated off Thoothukudi at a depth of around 305-310 m during April 2013. One female specimen of the said species was collected as an incidental by-catch in the trawl fisheries off Thoothukudi coast of Gulf of Mannar, from India, between 08º 35’ 22.5" N lat. 78º 27’ 40.9" E long and 08º 31’ 91.2"N lat. 78º 25’ 32.7"E long at a depth of 305-310 m. Ranninoides personatus Henderson, 1888, reported in India during (Alcock, 1896) from coast of  Bay of Bengal and further there are no published reports on occurrence of this species along the Thoothukudi coast of Gulf of Mannar.